MORPHOMETRY AND DIET OF Chrysichthys nigrodigitatus (Lecepede) IN MAJIDUN RIVER, IKORODU, LAGOS STATE, NIGERIA. - OGUNBANWO , O. M; ODU-ONIKOSI, S.G. (Nigerian Journal of Fisheries, 2022)
The study was conducted to investigate the sustainability and availability of Chrysichthys nigrodigitatus one of the most commercial fish found in Majidun River, Ikorodu between October, and December 2020. Fifty (50), fish specimens were collected from fishermen at the landing site, the major fishing methods employed by the fishermen were cast netting and set netting. The total length ranged from 11.00 to 30.00cm (mean size 19.67 ± 4.56cm) while the standard length ranged from 8.30 - 24.50cm (mean size 15.09 ± 3.39cm). The length weight relationship was described by the equation: Log W = 1.6373 + 2.88 LogSL and the condition factor ranged from 1.49 – 3.60. The results were obtained from the study of the stomach contents of the specimens in the laboratory using visual and microscopic examinations. Analysis of the stomach content were done by combination of frequency of occurrence methods and numerical methods were used to study the food. The diets revealed five (5) identified food items and unidentified mass. Sediments was the most abundant food items by occurrence (34.70%) followed by unidentified mass (19.80%) while crustaceans, molluscs, fishes, and insects were the least abundant with 17.82%, 16.83%, 6.93% and 3.92% respectively. Considering the numerical method, mollusks was the most abundant (97.4%), while insects was the least (0.23%).